Penguatan Perilaku Personal Hygiene melalui Game Edukatif pada Remaja SMAN 1 Tilatang Kamang (Jurnal Pengabdian Masyarakat Bina Usada (ABDINUSA), 2025)
Adolescence is a crucial stage in developing healthy lifestyle habits, one of which is personal hygiene, which plays an important role in preventing infectious diseases and reproductive health disorders. The lack of adolescents’ awareness of maintaining personal hygiene often leads to various health problems such as acne, body odor, skin infections, and vaginal discharge. This community service activity aimed to strengthen personal hygiene behavior through an educational approach based on fun and interactive games. The activity was carried out at SMAN 1 Tilatang Kamang and involved 98 students as participants. The methods included interactive counseling sessions, pre-test and post-test evaluations, and the implementation of educational games with personal hygiene themes. The results showed a significant improvement in students’ knowledge and attitudes toward personal hygiene, with approximately 90% of participants achieving higher post-test scores compared to pre-test results. Participants also demonstrated high enthusiasm throughout the activity. These findings indicate that educational games are an effective approach to enhance adolescents’ understanding and application of personal hygiene practices. It is expected that similar activities can be conducted continuously with the support of teachers, health workers, and parents to promote clean and healthy living habits in the school environment.